Significant Improvement of Acute Complete Spinal Cord Injury Patients Diagnosed by a Combined Criteria Implanted with NeuroRegen Scaffolds and Mesenchymal Stem Cells - Xiao, Zhifeng; Tang, Fengwu; Zhao, Yannan; Han, Guang; Yin, Na; Li, Xing; Chen, Bing; Han, Sufang; Jiang, Xianfeng; Yun, Chen; Zhao, Changyu; Cheng, Shixiang; et al. (Cell transplantation, 2018)
Stem cells and biomaterials transplantation hold a promising treatment for functional recovery in spinal cord injury (SCI) animal models. However, the functional recovery of complete SCI patients was still a huge challenge in clinic. Additionally, there is no clinical standard procedure available to diagnose precisely an acute patient as complete SCI. Here, two acute SCI patients, with injury at thoracic 11 (T11) and cervical 4 (C4) level respectively, were judged as complete injury by a stricter method combined with American Spinal Injury Association (ASIA) Impairment Scale, magnetic resonance imaging (MRI) and nerve electrophysiology. Collagen scaffolds, named NeuroRegen scaffolds, with human umbilical cord mesenchymal stem cells (MSCs) were transplanted into the injury site. During 1 year follow up, no obvious adverse symptoms related to the functional scaffolds implantation were found after treatment. The recovery of the sensory and motor functions was observed in the two patients. The sensory level expanded below the injury level, and the patients regained the sense function in bowel and bladder. The thoracic SCI patient could walk voluntary with the hip under the help of brace. The cervical SCI patient could raise his lower legs against the gravity in the wheelchair and shake his toes under control. The injury status of the two patients was improved from ASIA A complete injury to ASIA C incomplete injury. Furthermore, the improvement of sensory and motor functions was accompanied with the recovery of the interrupted neural conduction. These results showed that the supraspinal control of movements below the injury was regained by functional scaffolds implantation in the two patients who were judged as the complete injury with combined criteria, it suggested that functional scaffolds transplantation could serve as an effective treatment for acute complete SCI patients.